Physical and chemical properties of pineapple fruit of cv. Pada and cv. Sarawak in response to flowering hormones - Sam Nureszuan Sam Sabtu,; Noorasmah Saupi,; Shiamala Devi Ramaiya,; Fauziah Abu Bakar,; Phebe, Ding (Penerbit Universiti Kebangsaan Malaysia, 2022)
Pineapple flowering can be stimulated through artificially induced flowering (AIF) to ensure year-round production. The post effect gains from AIF is currently not universally acknowledged by previous studies, therefore, this study aims to evaluate the physical and chemical fruit properties in response to different AIF practices on cv. Pada, and cv. Sarawak. The AIF was applied to 9-month-old plants with nine treatments being tested, consisting of calcium carbide (CaC2 ), naphthaleneacetic acid (NAA), and ethephon at various concentrations. The fruit samples were collected at a maturity index of 5 in order to determine its physical (total fruit weight, fruit weight without crown, total fruit length, fruit length without crown, fruit diameter, peduncle length and peduncle diameter) and chemical properties (pH, total soluble solid and titratable acidity). The results showed that the total fruit weight as well as fruit weight without crown on cv. Pada and total fruit weight on cv. Sarawak were not affected by AIF treatments. The study showed a significantly higher fruit weight in T7 (low ethephon concentration) in comparison to T10 (high ethephon concentration) and T4 (NAA treatment) was recorded on cv. Sarawak. The trend of fruit length without crown on both cultivars decreased as the hormone concentration increased. The peduncle length exhibited significantly shorter in T3 (high CaC2 concentration) for cv. Pada, and T10 (high ethephon concentration) for cv. Sarawak at 30%, and 15% shorter than other treatments, respectively. In fruit chemical properties, TSS and TA on cv. Pada showed a significant difference, this particular result may have been influenced by an external factor such as the environmental conditions during the fruit ripening stage due to differing harvesting periods between the treatments. Overall, the study suggests that the AIF treatments may affect some of the physical and chemical fruit properties either via the direct or indirect response toward AIF.